Comparison of crevicular fluid cytokine levels after the application of surface sealants: a randomized trial - Şen, Sinan; Orhan, Gül; Zingler, Sebastian; Katsikogianni, Eleni; Lux, Christopher J.; Erber, Ralf (Journal of orofacial orthopedics, 2019)
Purpose Surface sealants are widely used in orthodontic practice to avoid enamel decalciﬁcations in patients treated with ﬁxed orthodontic appliances. While their clinical beneﬁt was tested in several studies, their biocompatibility has been evaluated to a lesser extent. Therefore, the aim of this randomized prospective study was to evaluate possible adverse biological effects of three commonly used surface sealants and a bonding primer on gingival tissues by analysing cytokines in crevicular ﬂuid of orthodontic patients after the application of surface sealants. - Methods A single centre parallel trial was conducted. Using a split-mouth design quadrants of 15 patients requiring orthodontic treatment with ﬁxed appliances were randomized to one of three commonly used surface sealants (Pro Seal®, Opal®Seal™, Protecto®CaF2Nano) and a bonding primer (Transbond™ XT). Interleukin (IL)-8 and IL-10 levels in crevicular ﬂuids of the individual quadrants were assessed at four different time points (before application, and at 30, 60 and 90 min after application). - Results In all, 60 quadrants of 15 patients were randomized (Pro Seal® n = 15, Opal®Seal™ n = 15, Protecto®CaF2Nano n = 15, Transbond™ XT n = 15) and analysed. No signiﬁcant changes for IL-8 or IL-10 levels in crevicular ﬂuid after the application of surface sealants or bonding primer were detected. However, interpatient variability was high. No further clinical side effects were detected. - Conclusions Commonly used pre-bonding surface sealants (Pro Seal®, Opal®Seal™) do not appear to have a signiﬁcant impact on inﬂammatory cytokines levels of crevicular ﬂuid and do not appear to contribute to sensitization or hypersensitivity events.
Gesehen am 02.03.2020